Further investigations of geomagnetic diurnal variations associated with the 2011 off the Pacific coast of Tohoku earthquake (Mw 9.0). (15th December 2015) - Han, Peng; Hattori, Katsumi; Xu, Guangjing; Ashida, Ryo; Chen, Chieh-Hung; Febriani, Febty; Yamaguchi, Hiroki
Highlights: A unique geomagnetic anomaly was detected against the 16 years background. We verified the geomagnetic anomalies reported byXu et al. (2013) . The anomaly was unlikely caused by strong geomagnetic storms or a statistical fluke. The anomaly was in agreement with seismicity anomaly and GPS anomaly. The anomaly is probably related to the preparation of the 2011 Tohoku earthquake. Abstract: As one of the most promising candidates for short-term earthquake forecasting, the seismo-electromagnetic phenomena have been intensively studied for several decades. Recently, Xu et al. (2013) have reported unusual behaviors of geomagnetic diurnal variations in the vertical component prior to the 2011 off the Pacific coast of Tohoku earthquake (Mw 9.0). To validate this result, further investigations have been applied in this study. Geomagnetic data of 16 years' long term observation have been analyzed using the same method in Xu et al. (2013). Ratios of diurnal variation range between the target station Esashi (ESA) which is about 130 km from the epicenter and the remote reference station Kakioka (KAK) about 300 km distant to the epicenter have been computed. After removing seasonal variations revealed by wavelet transform analysis, the 15-day mean values of the ratios in the vertical component shows a clear anomaly exceeding the statistical threshold about 2 months before the mega event. This anomaly is unique over a 16-year long background, and further discussions indicate that this anomaly is unlikely caused by strong geomagnetic storms or a statistical fluke. Therefore, this study has provided a strong support to the previous results in Xu et al. (2013).